Development of a cybersecurity framework for cloud environments adapted to the retail sector - Isidoro, T.; Coutinho, C.; Serrão, C. (2025 Third International Conference on Industry 4.0 Technology (I4Tech), 2025)
Retail companies are increasingly targeted by cyber threats that are becoming more complex and difficult to deal with as technologies evolve, particularly due to the complexity and volume of information involved in this type of business. Traditional solutions such as antivirus/antimalware are becoming insufficient to deal with mass attacks that are increasingly sophisticated given current computing power. The retail business, due to its characteristics, is becoming a greater target, due to the large number of transactions and potential points of intrusion, from employees to partners. This article proposes a cybersecurity framework to support the migration of on-premises systems to the cloud. This framework consists of controls aimed at increasing confidence in migration, which have been defined through the analysis of internationally recognized frameworks and the author's practical experience. The focus of this document is mainly on the retail sector and data protection.